PROVENANCE OF THE PERMIAN-TRIASSIC RED BEDS FROM THE EASTERN PART OF THE MOSCOW BASIN, EAST EUROPEAN PLATFORM: U-Pb LA-ICP-MS AND RAMAN SPECTROSCOPY DETRITAL ZIRCON DATA - A. V. Chistyakova; R. V. Veselovskiy; V. B. Khubanov; A. V. Ivanov; A. E. Marfin; N. V. Bryanskiy; V. K. Golubev (Геодинамика и тектонофизика, 2023)
We present the first systematic results of U-Pb LA-ICP-MS dating of detrital zircons from 12 samples representing different stratigraphic levels of 5 sections of the Permian-Triassic rocks, located within the eastern part of the Moscow basin (syneclise) – Zhukov ravine, Astashikha, Nedubrovo, Balebikha and Klykovo. It is shown that the accumulation of the Upper Permian and Lower Triassic terrigenous complexes occurred under the influence of competing sources with two contrasting provenance signals with Neoproterozoic (Vendian)-Paleozoic and Paleo-Mesoproterozoic ages. The identified provenance signal patterns were used to detail the correlation and stratigraphic subdivision of the Permian-Triassic terrigenous complex of the Moscow basin. Raman spectroscopy of detrital zircon, first applied to the Permian-Triassic rocks of the East European platform, made it possible to identify sedimentary complexes of a relatively older terrigenous basin as a separate source of zircons, which experienced superimposed thermal impact in the VendianCambrian time (~500–600 Ma).